A nonparametric test for intervention effect in Markov Regime Switching model - Talento, Mara Sherlin D.
Abstract (Highly volatile series data like those in the financial markets usually exhibit regime switching process whose behavior becomes more complicated when interventions like policy change or contagion induces effects on the model dynamics. We develop a method of testing presence of intervention effect in a Markov regime switching model. The test allows the regime to be affected by varying nature of interventions at different time points. A simulation study is designed to account for example different combination of intervention types, magnitude of intervention effect, and distance of two regimes. The simulation study exhibits that the test is correctly sized and powerful especially when the intervention effect is postulated to occur with a pulse-type intervention variable).
June 2018.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Markov regime switching; Markov Chain Monte Carlo; Nonparametric testing